Evaluasi Usability dengan Metode Heuristic Walkthrough (Studi Kasus: Website Beasiswa XYZ) - Muhammad Ilham Maksum; Buce Trias Hanggara; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The xyz scholarship website is a site developed for xyz scholarship recipients, a scholarship program organized by the xyz institution. The purpose of this site is to facilitate the management in monitoring, as well as to facilitate scholarship recipients in reporting. Then, from the user experience questionnaire (UEQ) that the researcher distributed to eleven respondents, the score for the newness scale of the xyz scholarship website was on an average of 0.31 and a comparison benchmark that was